Maternal and neonatal health skills of nurses working in primary health care centre of Eastern Nepal - Chaudhary, Ramanand; Karn, BK (Health Renaissance, 2017)
Background: Nepal has one of the world’s highest maternal and neonatal mortality. In Nepal, 73% of delivery is take place at home without trained attendant. Delivery by trained persons is 27% which reflects the need for attention of women's health in particular reproductive health. Objective: To assess knowledge and performance skills of nurses regarding maternal and neonatal health. Methods: Descriptive analytical study was carried out on nurses working in selected primary health care center of eastern region of Nepal. Random sampling technique was used to select 10 PHC and purposive sampling technique was used to select nurses in different primary health care center. Nurses were interviewed using pre-designed questionnaire and performance skill check list. Collected data were entered in SPSS 10.5 software package and analyzed. Results: The study showed that knowledge of auxillary nurse midwife/staff nurse was satisfactory in antenatal, intra-natal and post natal care of mother while they were relatively poor in newborn resuscitation. ANM/staff nurses showed very poor skills i.e. only 16.7%, 36.7% and 7% were competent in providing antenatal, intra-natal and post natal care respectively. Unfortunately none were found to be competent in newborn resuscitation. Conclusion: Birth handling competence levels are generally low in ANM/Staff nurses working in PHCCs Health Renaissance 2015;13 (1): 30-39